2023
DOI: 10.1038/s41598-023-37249-z
|View full text |Cite
|
Sign up to set email alerts
|

Foraging for selenium: a comparison between hyperaccumulator and non-accumulator plant species

Abstract: Selenium (Se) hyperaccumulators are a unique group of plants that can accumulate this element in their aerial parts at concentrations exceeding 100 mg kgDW−1. These plants actively search for Se in the soil, a phenomenon known as root foraging, reported to date only by few studies. In this study, the effect of localized Se enrichment, in the form of selenite and selenate, was investigated on the root architecture of two Se-hyperaccumulators (Stanleya pinnata and Astragalus bisulcatus) and two non-accumulators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Root growth responses may be an additional important mechanism of hyperaccumulation (e.g., Boyd et al, 2000;Chen et al, 2023;El Mehdawi et al, 2015;Haines, 2002;Montanari et al, 2023;Moradi et al, 2009;Pinto Irish et al, 2021;Rosatto et al, 2021;Tognacchini et al, 2020;Whiting et al, 2000). Of these root foraging studies, all but two have demonstrated positive root responses of hyperaccumulators to an element.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root growth responses may be an additional important mechanism of hyperaccumulation (e.g., Boyd et al, 2000;Chen et al, 2023;El Mehdawi et al, 2015;Haines, 2002;Montanari et al, 2023;Moradi et al, 2009;Pinto Irish et al, 2021;Rosatto et al, 2021;Tognacchini et al, 2020;Whiting et al, 2000). Of these root foraging studies, all but two have demonstrated positive root responses of hyperaccumulators to an element.…”
Section: Discussionmentioning
confidence: 99%
“…Of these root foraging studies, all but two have demonstrated positive root responses of hyperaccumulators to an element. These positive responses include root proliferation (Boyd et al, 2000;Haines, 2002;Montanari et al, 2023;Pinto Irish et al, 2021;Tognacchini et al, 2020), lateral branching and lateral length (Whiting et al, 2000), root hair length (Whiting et al, 2000), and directional growth (Mehdawi et al, 2015). Ni tolerance and root elongation of S. polygaloides and a congeneric nonhyperaccumulator, Streptanthus breweri A.…”
Section: Discussionmentioning
confidence: 99%
“…In all, 16 ZIP genes have been authenticated in A. thaliana [17], 14 ZIP genes in Vigna unguiculata [18], and 58 ZIP genes in wheat (Triticum aestivum), 44 of which are homologous to rice ZIP proteins [19]. In potato (Solanum tuberosum), 29 ZIP genes have been identified [20] Selenium (Se) is a nonmetallic element classified in Group 16 of the periodic table along with sulfur (S), due to its similar chemical properties [21]. Se exhibits various biological activities, including immune system support, antioxidant effects, antiviral properties, and anticancer potential [22].…”
Section: Introductionmentioning
confidence: 99%
“…Selenium (Se) is a nonmetallic element classified in Group 16 of the periodic table along with sulfur (S), due to its similar chemical properties [ 21 ]. Se exhibits various biological activities, including immune system support, antioxidant effects, antiviral properties, and anticancer potential [ 22 ].…”
Section: Introductionmentioning
confidence: 99%